Influence of pre-hospital to post-hospital delay factors on MI complications: a prospective cohort study - Akhter, Javeria; Khalid Naseeb; Ali, Sameera (Journal of the Pakistan Medical Association, 2024)
Objective: To identify factors contributing to delays in in the initiation of treatment among ST elevation myocardial infarction patients. Method: The prospective cohort study was conducted at the National Institute of Cardiovascular Disease, Karachi, from December 2020 to June 2021, and comprised ST elevation myocardial infarction patients of either gender aged at least 18 years. Time delay categories were 1st and 2nd delays that were patient-related, and 3rd delay that was system-related), with thresholds of 90 minutes and 120 minutes. Those who experienced delays were placed in group A, while the rest were in group B. Socio-demographic factors, co-morbidities, reasons of delay and in-hospital complications were recorded. Data was analysed using SPSS (version 21). Results: Of the 348 patients, 174(50%) were in group A; 129(74.1%) males and 45(25.9%) females with overall mean age 57.52±10.59 years. The remaining 174(50%) were in group B; 148(85.1%) males and 26(14.9%) females with overall mean age 54.4±12.1 years. The delays were associated with male gender, education level and employment status (p<0.05). Factors contributing to 1st delay included lack of cardiac symptom awareness 77(77%), belief in symptom resolution 38(38%), attributing symptoms to gastric issues 30(30%), and dependency 14(14%). Transportation issues 4(66.7%), indirect commutation 3(50%) and distance 82(47.1%) caused the 2nd delay, while improper referrals 2(50%) and decision delays of more than an hour 1(25%) were common in the 3rd delay. Moreover, 150(86.2%) experienced in-hospital complications, and 88(50.6%) encountered both pre- and post-percutaneous coronary intervention complications (p=0.01). Conclusions: Pre-hospital and post-hospital delaying factors had an impact on ST elevation myocardial infarction complications, highlighting the need for improved patient education on recognising cardiac symptoms and seeking timely medical attention to reduce ST elevation myocardial infarction complications. Key Words: Delay factors, ST elevation myocardial infarction, STEMI, Percutaneous coronary intervention, PCI, three delay model, Myocardial infraction complications.